LOCAL FOOD TRADITIONS AND STAPLE FOOD CONSUMPTION: A STUDY OF NASI ARON IN TOSARI VILLAGE - Alifah Nur Aini Fajrin; Muhamad Gunawan Ashari; Novfit Frima Akbar; Roshidan; L. Abdi Zaljalaliwal Ikrom (jses, 2025)
This journal is the result of direct research in the field, the Tengger tribe is an indigenous people who inhabit the highlands around the Bromo mountain area to be precise in Tosari Village, Pasuruan District, East Java Province. The purpose of making this journal is: to be able to find out the origins of the consumption of "aron rice" as a culinary food of the Tengger tribe. This food is usually served with a variety of vegetables and side dishes such as tempeh, tofu and chicken. Nasi Aron has a distinctive taste and is rich in spices. This food has its own uniqueness because the spices used use natural and traditional ingredients such as tamarind, cayenne pepper, galangal, and shallots. Nasi Aron is also a food that is part of the cultural identity of the Tengger tribe and is one of the favorite foods for the people in the area. Nasi Aron can also be a way to maintain the culture of the Tengger tribe which is unique and rich in cultural values.